(3GdJbQjQGJs - (3GdcdHGSj GdfLaj, eMeO EHQGgje Hf MSjf GdcdHGSj GdfLaj, hdO SfI (B1322(3g`s
(3ChdgG (B:s
(3ChdgG(B: (3bhdg aj GdYQhI ,EPG Tc aj (B... (3agPG GdfhY CYfj eTchc GdGWdGb hGdEVGaI dG jNJU HGdTHgGJ GdehVhYjI Hd jLQj aj GdTHgI GdeaghejIs
(3BNQgG (B:s
(3BNQgG(B: (3jhe GdCVMi jYfj GdUhe hjhe GdYGThQGA Ch jhe GdaWQ (B... (3hcPG JQi aj hOGY GdMSjf Ydjg GdSdGe dTgQ QeVGfs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdPQjYI, L (B4: 268s
(3GdPQjYI, L (B4: 268s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3CUhd Gdabgs